DOSES DE POTÁSSIO NA REDUÇÃO DA PODRIDÃO RADICULAR SECA DO FEIJOEIRO. - COSTA, Brenda Fernandes; PESSÔA, Guilherme Martins; ROSA, Artur Guerra; MIRANDA, Hevelâyne Cristina Ferreira; SANTOS, Stephany; GRAICHEN, Felipe André Sganzerla (ANAIS DO ENIC, 2022)
-